Efektifitas Media Kartu Bergambar Dalam Pembelajaran Bahasa Arab Kelas V MIN 42 Bireuen - Wildatun Zuhra; Muhammad Ediyani (Yayasan Madinah Al-Aziziyah, 2026)
The low level of Arabic vocabulary mastery among Madrasah Ibtidaiyah students remains a major problem in Arabic language learning, mainly due to the dominance of lecture and verbal memorization methods that lack context. This condition also occurs among fifth- grade students at MIN 42 Bireuen, as evidenced by low learning participation and unachieved classical mastery. “This study aims to analyze the effectiveness of using picture cards in improving the mastery of Arabic vocabulary among fifth-grade students at MIN 42 Bireuen. The study used a classroom action research (CAR) approach, which was carried out in two cycles with the stages of planning, implementation, observation, and reflection. There were 25 students in the study. Data were collected through vocabulary learning outcome tests and observation of learning activities, then analyzed quantitatively and descriptively. The results showed that the students' average scores increased from 56.40 in the pre-action to 65.68 in Cycle I and 82.32 in Cycle II, with the percentage of classical mastery increasing to 88%. These findings indicate that picture cards are an effective medium for improving students' mastery of mufradāt.” This study contributes empirically to strengthening the application of dual coding theory through a reflective and contextual two-cycle PTK design in Arabic language learning at Madrasah Ibtidaiyah.